2019
DOI: 10.1103/physrevd.100.125003
|View full text |Cite
|
Sign up to set email alerts
|

Fock quantization of the Dirac field in hybrid quantum cosmology: Relation with adiabatic states

Abstract: We study the relation between the Fock representations for a Dirac field given by the adiabatic scheme and the unique family of vacua with a unitarily implementable quantum evolution that is employed in hybrid quantum cosmology. This is done in the context of a perturbed flat cosmology that, in addition, is minimally coupled to fermionic perturbations. In our description, we use a canonical formulation for the entire system, formed by the underlying cosmological spacetime and all its perturbations. After intro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Ref. [85] analyzed the relation between these adiabatic states and our family of unitarily equivalent quantizations of the Dirac field, including those that satisfy the condition of asymptotic diagonalization. It was shown that the representations associated with adiabatic states of all orders belong to the same equivalence class.…”
Section: Uniqueness Of the Vacuum: Minkowski And De Sitter Spacetimesmentioning
confidence: 99%
“…Ref. [85] analyzed the relation between these adiabatic states and our family of unitarily equivalent quantizations of the Dirac field, including those that satisfy the condition of asymptotic diagonalization. It was shown that the representations associated with adiabatic states of all orders belong to the same equivalence class.…”
Section: Uniqueness Of the Vacuum: Minkowski And De Sitter Spacetimesmentioning
confidence: 99%
“…As we mentioned in the Introduction, the criteria of symmetry invariance and of unitary implementability of the quantum evolution have been successfully extended to select a unique preferred Fock representation for fermion fields in cosmological scenarios [46][47][48][49][50][51][52][53]. This and the uniqueness results here reviewed have been fruitfully exploited e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Apart from addressing the uniqueness of the quantization of free real scalar fields in FLRW spacetimes [13][14][15][41][42][43], the criteria were successfully employed to remove the ambiguities in the quantization of free (test) KG fields minimally coupled to a de Sitter background [44], as well as in anisotropic Bianchi I spacetimes [45]. It is worth remarking that the criteria of invariance and of unitarity have also been fruitfully exploited to single out a unique preferred quantum description for fermion fields in cosmological scenarios [46][47][48][49][50][51][52][53].…”
mentioning
confidence: 99%
“…In fact, suppose that, in our reference quantization (86), we switch the convention concerning particles and antiparticles for all modes corresponding to N 2 . This redefinition is effectively attained with the interchange f n l ↔ g n l (n ∈ N 2 ), as follows from the definition (79). Then, the behavior of the new coefficients λ f n would no longer be O(1) on N 2 , but they would behave (in norm) as…”
Section: Uniqueness Of the Quantizationmentioning
confidence: 99%
“…Ref. [79] analyzed the relation between these adiabatic states and our family of unitarily equivalent quantizations of the Dirac field, including those that satisfy the condition of asymptotic diagonalization. It was shown that the representations associated with adiabatic states of all orders belong to the same equivalence class.…”
Section: Uniqueness Of the Vacuum: Minkowski And De Sitter Spacetimesmentioning
confidence: 99%